The avian gut microbiota: Diversity, influencing factors, and future directions - Sun, Fengfei; Chen, Junfeng; Liu, Kai; Tang, Meizhen; Yang, Yuewei (Frontiers in Microbiology, 2022)
The gut microbiota is viewed as the “second genome” of animals, sharing intricate relationships with their respective hosts. Because the gut microbial community and its diversity are affected by many intrinsic and extrinsic factors, studying intestinal microbes has become an important research topic. However, publications are dominated by studies on domestic or captive birds; research on the composition and response mechanism of environmental changes in the gut microbiota of wild birds remains scarce. Therefore, it is important to understand the co-evolution of host and intestinal bacteria under natural conditions to elucidate the diversity, maintenance mechanisms, and functions of gut microbes in wild birds. Here, the existing knowledge of gut microbiota in captive and wild birds is summarized, along with previous studies on the composition and function, research methods employed, and factors influencing the avian gut microbial communities. Furthermore, research hotspots and directions were also discussed to identify the dynamics of the avian gut microbiota, aiming to contribute to studies of avian microbiology in the future.